ANALISIS KONTEN DAKWAH REMAJA DALAM AKUN TIKTOK @KADAM SIDIQ - Ahmad Adnan; Naufal (STAI DI AL-HIKMAH, 2024)
This study aims to determine the content of youth preaching content contained in the Kadam Sidiq Tiktok account. This study uses a qualitative method with a content analysis method. Data collection was carried out through observation and documentation. The object of the study was the Kadam Sidiq Tiktok video content that was broadcast on the Kadam Siddiq Tiktok account from January to April 2022. The conclusion of this study is that there is content related to current youth problems, namely quoting Ali bin Thalib's quote from Google, rushing to pray, women who do not wear the hijab are reprimanded by their mothers, a trend of writing